Integrasi Psikologi Barat dan Islam: Sebuah Literature Review tentang Epistemologi, Pendidikan, dan Konseling - Hamidah Hamidah; Mu’alimin Mu’alimin; Mukffan Mukffan (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
The integration of Western psychology and Islamic perspectives has become an important issue in the development of contemporary science and education. The rapid advancement of modern psychology calls for a synthesis with the epistemological framework of Islam to be more contextual in addressing academic and practical needs, particularly in the fields of education, counseling, and character development. This article aims to answer the research question: How is the trend of integration between Western psychology and Islamic perspectives in the current literature, and what are the implications for Islamic education theory and practice? This study uses a literature review method with a qualitative approach. Articles were collected via Google Scholar and the Publish or Perish application using the keywords "integration of psychology" AND "Islamic education." From the initial 40 articles, the screening process resulted in 5 (five) articles that met the publication year criteria (2021–2025), topic relevance, and open access. The review results show three main themes: (1) epistemological integration emphasizing the Islamization of knowledge; (2) the application of Islamic psychology in education, counseling, and curriculum; and (3) conceptual and practical challenges in connecting Western psychology with the Islamic paradigm. This literature synthesis highlights the importance of an integrative framework to strengthen the relevance of Islamic psychology in both academic and social domains. Future studies need to expand empirical methodologies and deepen the development of cross-disciplinary applicative models.